Robot-assisted knee arthroplasty: Analyzing the learning curve and initial institutional experience - Leandro Ejnisman; Eliane Antonioli; Luciana Cintra; Pamela Gabriela de Oliveira Souza; Lauro Augusto Veloso Costa; Mario Lenza (Computational and Structural Biotechnology Journal)
Robot-assisted total knee arthroplasty (rTKA) involves a learning curve for orthopedic surgeons. The aim of the present study was to assess the surgical times of rTKA procedures performed by initial stage and proficiency stage surgeons in comparison with times of conventional total knee arthroplasty (cTKA). The results reveal that the learning curve for rTKA varies considerable between surgeons, suggesting that the skill and aptitude of the individual to adapt to the robotic system play key roles in the learning process. Proficiency stage surgeons were able to reduce rTKA surgical times to levels comparable with those of conventional surgeries after performing approximately 30 to 40 robotic procedures. Ongoing research has shown promising outcomes in terms of improved clinical results and reduced complications following the application of advanced robotic technology to total knee arthroplasty.